Writing and rewriting the Holocaust : narrative and the consequences of interpretation - Young, James Edward (Indiana University Press, 1990)
A carefully prepared historiographical work interprets the meaning of Holocaust literature as it examines the perpetuation of Holocaust memory and understanding in several forms of media studied ... Includes an extensive bibliography of works.